Association between psychological distress and dietary intake among evacuees after the Great East Japan Earthquake in a cross-sectional study: the Fukushima Health Management Survey. Issue 7 (5th July 2016) - Uemura, Mayu; Ohira, Tetsuya; Yasumura, Seiji; Otsuru, Akira; Maeda, Masaharu; Harigane, Mayumi; Horikoshi, Naoko; Suzuki, Yuriko; Yabe, Hirooki; Takahashi, Hideto; Nagai, Masato; Nakano, Hironori; et al.
Abstract : Objective: Psychological distress is generally associated with poor dietary intake, but this has never been investigated among residents after a major disaster. We attempted to reveal the associations between dietary intake and non-specific mental health distress as well as traumatic symptoms among evacuees after the Great East Japan Earthquake of 2011. Methods: In this cross-sectional analysis of 63 047 evacuees (27 901 men, 35 146 women) who responded to The Fukushima Health Management Survey in 2012, non-specific mental health distress was assessed using the Kessler-6 (K6) scale, while traumatic symptoms were evaluated using the Post-traumatic Stress Disorder (PTSD) Checklist—Stressor-Specific Version (PCL-S). The outcome was 'low frequency'—meaning a daily consumption in the 25th centile or less according to the food frequency questionnaire (FFQ)—of 19 targeted food items. Logistic regression analysis was used to estimate ORs and 95% CIs adjusted for demographic, lifestyle-related and disaster-related factors. Results: Of the participants, 14.7% suffered non-specific mental health distress, and 21.2% exhibited traumatic symptoms. Multivariable adjusted logistic regression analysis showed that the former were likely to have a low intake frequency of certain foods, such as rice and bread, fish, meat, vegetables or fruit (non-juice), soya bean products, milk, and yogurt or lactobacillus drinks; the latter were also likely to have a low intake frequency of certain foods, including rice and bread, fish, meat, vegetables (non-juice), milk and yogurt or lactobacillus drinks, but conversely consumed vegetable and fruit juices more often. These associations between dietary intake and non-specific mental health distress, as well as traumatic symptoms, were predominantly observed in women. Conclusions: Psychological distress after the Great East Japan Earthquake among evacuees was associated with a low intake frequency of certain foods, and the association was predominantly observed in women.